A Systematic Literature Review of Interactive E-Modules Integrating Collaboration and Local Wisdom to Foster Students’ Problem-Solving Skills and Character - Udani, Ketut Sri Naya; Ardana, I Made; Suweken, Gede (Darul Yasin Al Sys, 2025)
Although interactive e-modules in mathematics education have attracted growing scholarly interest, limited research has addressed the integration of collaboration and local wisdom to simultaneously enhance students’ problem-solving skills and character development. This study systematically reviews prior empirical research on interactive e-modules to examine their distribution across educational levels, evaluate their impact on cognitive and character-related outcomes, and identify existing gaps and future directions. Adopting a Systematic Literature Review (SLR) approach guided by the PRISMA framework, 15 peer-reviewed studies published between 2020 and 2025 were analyzed, sourced from Google Scholar and Scopus databases. Descriptive and thematic analyses reveal that most studies focused on junior high school contexts and employed pedagogical models such as Problem-Based Learning (PBL), STEAM, Realistic Mathematics Education (RME), and Ethnomathematics, all of which demonstrated effectiveness in enhancing mathematical problem-solving abilities. However, integration of Social Emotional Learning (SEL) and local wisdom—such as the Tri Hita Karana philosophy—was relatively rare, despite their potential to cultivate values like empathy, responsibility, and environmental awareness. The findings contribute to the theoretical advancement of constructivist and sociocultural learning paradigms by underscoring the value of culturally and emotionally responsive digital content. The study concludes that interactive e-modules designed with collaborative and local cultural elements are instrumental in promoting holistic learning that supports both academic and character development. It recommends cross-sector collaboration among educators, families, and policymakers to design and implement contextually grounded e-modules. This review also identifies avenues for future research, including multi-level educational implementation, family involvement, and the integration of emotional learning in digital instructional design.